Gamification-Based Blended Learning in EFL Classroom: An Effectiveness Study - Hermi Zaswita; Doni Tri Putra Yanto; Hesti Leviana Sari (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2026)
This study investigates the effectiveness of gamification-based blended learning in improving student learning outcomes in an English as a Foreign Language (EFL) context. The research addresses the challenge of low student motivation and poor academic results in traditional courses. The study employed a pre-experimental One- Group Pretest-Posttest design with 40 students from an English Education program taking an Introduction to Sociolinguistics course. The blended learning approach incorporated gamification through the Wayground platform. The effectiveness of this approach was measured by comparing students' pretest and posttest scores. The analysis, conducted using SPSS Version 30, showed a significant increase in the average student score, from 70.60 on the pretest to 77.75 on the posttest. A paired-samples t-test confirmed this difference was statistically significant (p < .001), while a Cohen's d Effect Size analysis revealed a large effect (d = 0.943). These findings indicate that the gamification-based blended learning model is highly effective and has a substantial positive impact on students' academic performance. The study reinforces that integrating digital technology and game elements enhances learning and directly contributes to improved student learning outcomes. The results suggest that this innovative approach can serve as a valuable reference for developing effective digital curricula and improving the quality of language learning in higher education.